Pemberdayaan Masyarakat Petani Kopi Lego Menuju Agrowisata Berkelanjutan dalam Perspektif Pentahelix Model di Gombengsari, Kabupaten Banyuwangi - Ratih Apri Utami; Nurul Dwi Novikarumsari (Fakultas Pertanian Universitas Jember, 2022)
Kampong Kopi Lerek Gombengsari (Kopi Lego) is a brand for Banyuwangi coffee plantation tourism activities starting from Gombengsari village. The development of Kopi Lego agro-tourism not only provides coffee tourism but is also supported by the role of Farmer Groups (Poktan) in the on-farm process and the role of Kelompok Sadar Wisata (Pokdarwis) in the coffee off-farm process through their supporting business units. Kopilego agro-tourism develops through the active participation of farmers in the Poktan and Pokdarwis institutional systems which have the potential to be developed through an empowerment model. There are several problems related to institutional management through Poktan and Pokdarwis including the low knowledge of member farmers in post-harvest coffee maintenance, both processing and marketing access and there is no synergistic support from various parties in sustainable agro-tourism management through Poktan and Pokdarwis institutions. This study aims to determine the institutional profile of Poktan and Pokdarwis Agrotourism, group empowerment in increasing the knowledge of Poktan and Pokdarwis members and analyze the empowerment that supports sustainable agro-tourism in the perspective of the penta helix model. This study uses a qualitative approach using the case study method. Data was collected by conducting in-depth interviews and literature review. The results showed that (1) Tunas Harapan Farmer Group and Pokdarwis Gombengsari became the main actors in the development of agro-tourism through the on-farm and off-farm processes of Lego Coffee, (2) empowerment of Poktan and Pokdarwis required assistance in processing and marketing access, and (3) Group-based empowerment involves various stakeholder roles in the pentahelix perspective (academics: UNEJ and UPN-VJ; business: BNI and Pertamina, community: Poktan and Pokdarwis; government: Department of Agriculture, Department of Industry and Trade and Department of Tourism; and media: Radar and Media Banyuwangi Social Affairs) to support sustainable agro-tourism in Gombengsari, Banyuwangi Regency.